Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Olmos family (all smiling): Mario's brother, Delores Olmos, Mary Louise Frampton holding Margaret Olmos, Judge Mario Olmos, son Daniel Olmos, Mario's sister and father, Fidel Olmos. Law Offices of Olmos and Frampton at 925 N St. #150, Fresno